IMPROVING SKILLS OF WRITING DESCRIPTION THROUGH BRAIN-BASED LEARNING LEARNING STUDENTS OF CLASS III SDIT AVICENNA BEKASI-UTARA - Leni Lidia; Fathiaty Murtadho; Fahrurrozi Fahrurrozi (JURNAL HANDAYANI PGSD FIP UNIMED, 2019)
Abstract:Research objectives to improve the results of learning to write the description through learning brain-based learning. The subject of the grade three research in Elementary Islamic school Avicenna North Bekasi. As many as 30 students. data collection techniques used IE test and non-test (observation). Based on a comparison of the results of the final study on cycle I: cycle II as much as 67%: 100%. Comparison of the results of the study are based on an average cycle I: cycle II is 75:89. Comparative score maximum cycle I: cycle II is 82:94. Comparative score of at least cycle I: cycle II is 70:87. Based on a comparison of the results of each study cycle of an increase in the success of the study. Keywords : writing skill, description, brain based learning Abstrak:Tujuan penelitian untuk meningkatkan hasil belajar menulis deskripsi melalui pembelajaran brain based learning. Subjek penelitian  siswa kelas III  SDIT Avicenna Bekasi Utara. Sebanyak 30 siswa . teknik pengumpulan data yang digunakan yaitu   tes dan non tes (observasi). Berdasarkan perbandingan hasil belajar ketuntasan pada siklus I : siklus II sebanyak 67% : 100%. Perbandingan hasil belajar berdasarkan rata-rata siklus I : siklus II adalah 75 : 89. Perbandingan skor maksimal siklus I : siklus II adalah 82 : 94. Perbandingan skor minimal siklus I : siklus II adalah 70 : 87. Berdasarkan perbandingan hasil belajar tiap siklus adanya peningkatan keberhasilan belajar. Kata Kunci:  Keterampilan menulis, deskripsi, brain based learning